Exploring the impact of dynamic capabilities on entrepreneurial orientation in healthcare organizations: Findings from symmetric and asymmetric modeling - Bouhalleb, Arafet; Messeghem, Karim (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2024)
This work considers strategic flexibility (SF), structural flexibility (SX) and information acquisition (IA) as dynamic capabilities that promote entrepreneurial orientation in the health sector. Based on a quantitative survey carried out with managers of healthcare organizations in France, we demonstrate that IA positively impacts EO and that SF mediates the IA–EO relationship. The findings also indicate that SX moderates the effect of SF on EO. Our research has relevant theoretical implications because it extends the entrepreneurship literature through a novel focus on EO determinants in the healthcare sector. Practical implications for managers and decision-makers are also noted. The findings offer insights to healthcare care managers that will allow them to review the management method to fully involve and engage teams and to be more entrepreneurial.